Efektifitas Badan Usaha Milik Desa (Bumdes) Di Desa Bulogading Kecamatan Bontonompo Kabupaten Gowa - Anas, Aswar; Madani, Muhlis; Tahir, Nurbiah (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2020)
This study examined the effectiveness of "Abbulogading" Village Enterprises (BUMDes) in 2018 in Bulogading Village, Bontonompo District, Gowa Regency. The purpose of this study was to determine the effectiveness of the management of village-owned enterprises in increasing community independence and strengthening the village economy. This study used Purpuporsive Sampling technique with the number of informants as many as 5 people through decision studies and field studies consisting of documentation interviews and observations then analyzed qualitatively The Results of this study showed that the presence of BUMDes in the village of Bulogading could help and increase productivity in the form of  profits in 2018, aspects of the efficiency of the use of organizational resources for the development of BUMDes seen from cooperation between members, aspects of satisfaction in the form of meeting the needs of employees / administrators in managing BUMDes, aspects of adaptation included employee / management responses, to know how effective the BUMDes itself  and community responses about the presence of BUMDes in serving the needs of the community and the survival aspects of the Bulogading village community.